RELATIONSHIP BETWEEN LAND COVER AND VEGETATION INDICES. CASE STUDY: EGHLID PLAIN, FARS PROVINCE, IRAN. - Marzieh MOKARRAM; Ali Darvishi BOLOORANI; Majid HOJATI (European Journal of Geography)
In this study, the Visible Atmospherically Resistant Index (VARI), Weighted Difference Vegetation Index (WDRVI), Enhanced Vegetation Index (EVI), Optimized Soil-Adjusted Vegetation Index (OSAVI), Atmospherically resistant vegetation index (ARVI), SAVI (Soil Adjusted Vegetation Index(, NDVI (Normalized Difference Vegetation Index) vegetation indices by Landsat 8 ETM+ bands vegetation in the Eghlid city, Fars province, Iran in 2015 were calculated. Then indexes compared with land cover map were calculated in order to determine the best index for making the land cover map of the region. The results showed that the area of Perennial forbs has different features than other land covers. WDRVI and SAVI showed the highest and lowest accuracies